Direct measurement of a patient's entrance skin dose during pediatric cardiac catheterization - Sun, Lue (J Radiat Res, 2014)
Children with complex congenital heart diseases often require repeated cardiac catheterization; however, children are more radiosensitive than adults. Therefore, radiation-induced carcinogenesis is an important consideration for children who undergo those procedures. We measured entrance skin doses (ESDs) using radio-photoluminescence dosimeter (RPLD) chips during cardiac catheterization for 15 pediatric patients (median age, 1.92 years; males, n = 9; females, n = 6) with cardiac diseases. Four RPLD chips were placed on the patient's posterior and right side of the chest. Correlations between maximum ESD and dose–area products (DAP), total number of frames, total fluoroscopic time, number of cine runs, cumulative dose at the interventional reference point (IRP), body weight, chest thickness, and height were analyzed. The maximum ESD was 80 ± 59 (mean ± standard deviation) mGy. Maximum ESD closely correlated with both DAP (r = 0.78) and cumulative dose at the IRP (r = 0.82). Maximum ESD for coiling and ballooning tended to be higher than that for ablation, balloon atrial septostomy, and diagnostic procedures. In conclusion, we directly measured ESD using RPLD chips and found that maximum ESD could be estimated in real-time using angiographic parameters, such as DAP and cumulative dose at the IRP. Children requiring repeated catheterizations would be exposed to high radiation levels throughout their lives, although treatment influences radiation dose. Therefore, the radiation dose associated with individual cardiac catheterizations should be analyzed, and the effects of radiation throughout the lives of such patients should be followed.